2009
DOI: 10.1007/s10916-009-9347-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Dental Deformities in Cephalometry Images Using Support Vector Machine

Abstract: This paper proposes an automated target recognition algorithm using Support Vector Machine (SVM) to extract landmark points for craniofacial features in cephalometry radiograph. The features are extracted by subjecting the radiograph to the Projected Principle Edge Distribution (PPED) algorithm. Edge flags are accumulated in every four columns and spatial distribution of edge flags are represented by a histogram. The resultants are the front end of support vector machine. Vectors, which possess land marks, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Examples are bone disease classification using collected 3D image analysis and the artificial intelligence diagnosis of dental deformities in cephalometry images using a support vector machine. 53,54 Neural networks or computers are used to record and categorize patterns using the collected and recorded information, which in turn is the basis for data mining analysis and anomaly detections. Examples are electroencephalogram (EEG) recordings for a better description of sleep, automatic classification of long-term ambulatory electrocardiogram (ECG) records according to type of ischemic heart disease, automated detection of neonate EEG sleep stages, epileptic seizure detection in EEGs using time-frequency analysis, central sleep apnea detection from ECG-derived respiratory signals, a detection of Alzheimer’s disease using independent component analysis (ICA)-enhanced EEG measurements, and epileptic EEG signal detection using time-frequency distributions.…”
Section: Resultsmentioning
confidence: 99%
“…Examples are bone disease classification using collected 3D image analysis and the artificial intelligence diagnosis of dental deformities in cephalometry images using a support vector machine. 53,54 Neural networks or computers are used to record and categorize patterns using the collected and recorded information, which in turn is the basis for data mining analysis and anomaly detections. Examples are electroencephalogram (EEG) recordings for a better description of sleep, automatic classification of long-term ambulatory electrocardiogram (ECG) records according to type of ischemic heart disease, automated detection of neonate EEG sleep stages, epileptic seizure detection in EEGs using time-frequency analysis, central sleep apnea detection from ECG-derived respiratory signals, a detection of Alzheimer’s disease using independent component analysis (ICA)-enhanced EEG measurements, and epileptic EEG signal detection using time-frequency distributions.…”
Section: Resultsmentioning
confidence: 99%
“…Support vector machine was previously used to diagnose dental deformities in cephalometry images and was found to be helpful in assisting dentists to quickly arrive at a conclusion whether a patient has been affected by any dental deformities or not. [13] The presented study is the first to use algorithmic systems for diagnosing periodontal diseases and also it is the first to compare the results of three different algorithms in predicting the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] ANNs, DT, and SVM were also compared with each other and performed for prediction models. [9] Although there are a few studies in dental area with the use of ANNs [10][11][12] and SVM, [13] there exist no available data for diagnosing and classification of periodontal diseases with the use of different types of algorithms alone or that compare the differences between each other.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, angles between various landmark points are calculated to find out the deformities in the dento-facial growth. Banumathi A. et al [94] used in this study the Projected Principal Edge Distribution (PPED) vectors as a system for medical image recognition, and was used also in image recognition system dicussed above described by Tanikawa C et al [80], as this techniques proved to provide better results.…”
Section: Cephalometrics Analysismentioning
confidence: 99%
“…In 2011 Banumathi A et al suggested [94] Another diagnostic model, Artificial intelligence role in dentofacial deformities diagnosis was discussed. The dentist must be familiar with morphological and functional maturity also oral surgeon and the orthodontist should be able to relate this knowledge to specific clinical problems such as skeletal mealocclusion and craniofacial anomalies.…”
Section: Cephalometrics Analysismentioning
confidence: 99%